Analysis and Handling of STA 1+325 SD 1+475 Embankments in the Construction of the IKN Toll Road, Balang Island Bridge Segment – Sp. Riko - Marnida Aryani; Toto Mochamad Taufik; Salman Alfaridzi (Journal of Engineering, Electrical and Informatics, 2025)
The construction of the IKN Toll Road on the Balang Island Bridge – Sp. Riko segment serves as a strategic infrastructure project aimed at enhancing connectivity and accelerating regional development in the Indonesian Capital City area. However, within the STA 1+325 to STA 1+475 section, complex geotechnical challenges were identified due to the subgrade’s low bearing capacity and high consolidation potential. These conditions threaten the embankment’s stability, which could affect construction quality and long-term performance. This study analyzes the subgrade characteristics, evaluates embankment stability, and proposes effective improvement methods based on geotechnical design standards. Field investigations, including sondir testing, soil laboratory analyses, and numerical simulations using PLAXIS finite element software, were conducted. The analysis involved assessing bearing capacity, consolidation settlement, and slope stability under both normal and seismic conditions. The selected improvement method—subgrade replacement with a 2.0-meter-thick material—successfully increased the safety factor to 1.715 under service conditions and 1.258 under earthquake conditions, while reducing potential settlement to acceptable limits. These results demonstrate that the replacement method effectively enhances embankment stability and ground performance. Hence, this technique is recommended as a reliable geotechnical solution for toll road and other infrastructure projects facing similar subgrade challenges.